2014
DOI: 10.1093/jxb/eru211
|View full text |Cite
|
Sign up to set email alerts
|

The non-catalytic N-terminal domain of ACS7 is involved in the post-translational regulation of this gene in Arabidopsis

Abstract: Post-transcriptional control of the expression of the 1-aminocyclopropane-1-carboxylate synthase (ACS) gene family is important for maintaining appropriate levels of ethylene production. However, the molecular mechanism underlying the post-transcriptional regulation of type 3 ACS proteins remains unclear. Multiple sequence alignment revealed that the N-terminus of type 3 ACSs was longer than that of other ACSs. Fusing the N-terminal 54 residues of ACS7, the sole type 3 ACS in Arabidopsis, to the β-glucuronidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 30 publications
4
43
0
1
Order By: Relevance
“…hormone levels, developmental transitions). Light affects ACS stability both positively and negatively; for instance, turnover of ACS5 is decreased (Yoon and Kieber, 2013a), whereas ACS7 turnover is increased (Xiong et al, 2014) by light. Exogenous cytokinin and brassinosteroid treatments increase ethylene production via posttranslational stabilization (Woeste et al, 1999;Hansen et al, 2009), and pathogen infection increases ACS abundance at both transcriptional and posttranslational levels (Han et al, 2010;Li et al, 2012).…”
Section: Keeping Synthesis On a Short Leashmentioning
confidence: 99%
See 4 more Smart Citations
“…hormone levels, developmental transitions). Light affects ACS stability both positively and negatively; for instance, turnover of ACS5 is decreased (Yoon and Kieber, 2013a), whereas ACS7 turnover is increased (Xiong et al, 2014) by light. Exogenous cytokinin and brassinosteroid treatments increase ethylene production via posttranslational stabilization (Woeste et al, 1999;Hansen et al, 2009), and pathogen infection increases ACS abundance at both transcriptional and posttranslational levels (Han et al, 2010;Li et al, 2012).…”
Section: Keeping Synthesis On a Short Leashmentioning
confidence: 99%
“…Predicted target sites for regulators are present (*) or absent (gray shading) but untested in several ACS isozymes. Protein half-lives have been measured for ACS6, SlACS2, ACS7, and ACS5 (Chae et al, 2003;Joo et al, 2008;Kamiyoshihara et al, 2010;Xiong et al, 2014); for epitopetagged reporters, the tag is indicated (myc, HA, or Flag). C, A complex overlay of motifs surrounds the TOE sequence in type 2 isozymes.…”
Section: Phosphorylation and Proteasome-mediated Degradation: Leitmotmentioning
confidence: 99%
See 3 more Smart Citations